Overcoding and Undercoding In The Topic “All Eyes on Rafah”: Research on BBC Indonesia and DETIKCOM’S News Article - Harahap, Evi Marlina; Nasution, Arie Azhari (Jurnal Hata Poda, 2024)
This paper is based on the desire to observe the act of linguistic operation that use the topic of ‘all eyes on Rafah’ that posted by BBC Indonesia and Detikcom. The problem in this paper is how the act of overcoding and undercoding operated in the teks. Both of the problems are studied with the use of Semiotics from Umberto Eco. The consept that offered by Eco are overcoding and undercoding. Overcoding is the operation of sign that derivated to a subsign-subsign. Overcoding changes signs to a more analytic. Undercoding is an operation of subsign that derivated to the original sign. Undercoding changes the subsign to be more familiar based on general trend. The method used is the method of qualitative. The analysis of that are built inductively, from the exclusive theme to inclusive’s, then the researcher will make some interpretation of the meaning of data. The data will analyze with analitical and typological instrument. Typological analysis is the classification of processing data to the groups, sets, or category based on clear criteria. Criteria that used in this paper are overcoding and undercoding. The result of research showed that the articles that posted by BBC and Detikcom used more overcoding than undercoding. Overcoding produce subsign that is more analytical. Meanwhile, undercoding produce sign dari derived from general trend. Overcoding making text be more analytical and esthetic, while undercoding makes the text more familiar. Therefore, both articles focus more on the analytical and esthetic side than the familiarity because it is assumed that the topic is already viral so the writers felt there is no need to gain more readers.